The Humanistic Perspective of Creativity in the Discourse of Involved Educators - Irena Wojnar and Janusz Korczak - Halina Monika Wróblewska (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: The role of the educator is to reflect on the processes of creation, co-creation and self-creation of man. One of the areas of social experience is concern about the fate of man in the modern world. The second area is the sense-forming activity present in experiments. Research Aim: The presented study is an attempt to present the issue of the humanistic perspective of creativity present in the discourse of educators distinguished in their involvement in the affairs of other people - Irena Wojnar and Janusz Korczak. Evidence-based Facts: Creativity is one of the most important concepts of the humanistic concept, which, describing the nature of man, emphasizes the individual's ability to actualize himself. Self-fulfillment means the readiness to set long-term tasks and the ability to carry them out, experiencing satisfaction from solving challenges that are a challenge for the individual. Changes in the surrounding world and one's own situation in the world, inscribed in the idea of the process of self-realization, are also related to the essence of human transgressive activity. Pointing to the important role of art in deepening human self-knowledge, one should refer to sources other than artistic ones. Summary: In the light of the experience of the involved educators, a dialogue takes place, which sets a new vision of human life in the future. The common concern of educators is the image of the world, the human condition and experience. Dialogue with human experience and the experienced human world is part of the concept of education, which opens the subjectivity of the individual and prepares them for intentional and effective activities for creative adaptation. The perspective of art that defines experience - combined with the perspective of experiencing life as art - is a valuable source of pedagogical reflection. The meeting of the involved educators - Humanists Irena Wojnar and Janusz Korczak - makes the discourse open to new readings and (re) interpretations.